Effectiveness of growth hormone therapy in children with Noonan syndrome - Eun mi Seok; Hong Kyu Park; Jung Gi Rho; Change Dae Kum; Hae Sang Lee; Jin Soon Hwang (Korean Society of Pediatric Endocrinology, 2020)
Purpose Recombinant human growth hormone (rhGH) has been used to improve growth in children with Noonan syndrome (NS). This study aimed to investigate the efficacy of rhGH therapy in Korean children with NS. Methods Seventeen prepubertal children (10 boys, 7 girls) with NS who received rhGH therapy for at least 3 years between 2008 and 2017 were included. To compare the response, age- and sex-matched children with GH deficiency (GHD; n=31) were included. Height and growth velocity before and during treatment were analyzed. Results The mean age of NS patients was 6.34±2.32 years. After treatment, the height standard deviation score (SDS) increased from -2.93±0.81 to -1.51±1.00 in patients with NS and from -2.45±0.42 to -1.09±0.47 in patients with GHD. There were no significant differences in growth velocity or change in height SDS between patients with NS and GHD. Growth velocity in the first year of treatment was higher in patients with PTPN11 mutations than those without PTPN11 mutations, but the change in height SDS was not significantly different between those 2 groups. Conclusions rhGH therapy can increase linear growth in prepubertal children with NS. The growth response between patients with NS and patients with GHD was not significantly different. Furthermore, we observed that lower doses of growth hormone have a similar effect on height compared to previous studies in patients with NS. Our study indicates that rhGH treatment is useful for growth promotion.